Information Technology-Based Financial Administration Training for Waste Bank Management - Supiin, Prima Prihatini (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background:  Currently there are many movements to support the government related to improving people's welfare by processing waste. Since the Covid-19 pandemic, the price of used waste has decreased. This community service is carried out at the “Gemi Nastiti” Waste Bank. The recap of activities and finances carried out at the “Gemi Nastiti” Waste Bank is done manually, this is because members do not yet have the knowledge and ability to do administration. Therefore, this community service aims to provide assistance in preparing technology-based administration. Contribution:  Providing knowledge, understanding, and financial administration skills to Waste Bank Managers "Gemi Nastiti" through the use of Microsoft excel and can input and apply Microsoft excel in processing their waste bank financial administration work. Method:  Providing material theoretically microsoft excel, demonstrating how to use microsoft excel, training and assistance in inputting financial transaction data, case solving from the field. Results:  The knowledge of the waste bank management "Gemi Nastiti" about Microsoft excell is approximately 10% at the time of the pre-test, while the work done is administration which has been done manually. For this reason, in the activities in the community that are currently carried out, namely financial administration training using Microsoft Excel, after the completion of the training, the post-test value obtained is on average 77%. Conclusion:  The administrators of the "Gemi Nastiti" waste bank can use Microsoft Excel in recording financial administration as evidence and information from the running of waste bank activities